If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x+27)=6x
We move all terms to the left:
3(x+27)-(6x)=0
We add all the numbers together, and all the variables
-6x+3(x+27)=0
We multiply parentheses
-6x+3x+81=0
We add all the numbers together, and all the variables
-3x+81=0
We move all terms containing x to the left, all other terms to the right
-3x=-81
x=-81/-3
x=+27
| B+99=126b= | | -6v-4=v-4 | | -3.8g+5+2.7g=2.7 | | 3x-2(6x-1)=10-4x+8-5x | | -1+x4=-6 | | 5x+72-x=180 | | (3x+1)/2=8 | | x-9/4=11 | | c/4-3=-8 | | g−8=25 | | 2x-11+14=180 | | 2(12-y)=-2(y-17)-10 | | 5x20=3x+6 | | 32+x=105x= | | 4x+5/3=9 | | 5j=6j+10 | | -2(3-6x)+5x=-159 | | 10=c/3——“8. | | 2=p+15/3 | | 4p/3=8/7 | | 5+7x=7x+15 | | 6(4a+8)=5(5a+8) | | -5x+8x+20=-5x-22+12x-6 | | 6+n=n+6 | | 9s-20=61 | | 3x+19+5=115 | | F(-3)=3x^2+4x-7 | | 8n-30=6(7n-5) | | 7-5x=-4x+15 | | 5x-47+2x+32+90=180 | | 2x+106=4x+38 | | 7r+9+8=52 |